Robin Hood - McSpadden, J. Walker (Joseph Walker), 1874-1960.; Hildebrandt, Greg.; McSpadden, J. Walker (Joseph Walker), 1874-1960. (Morris Plains, N.J. : Unicorn Pub. House, 1990)
Recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor.
Keywords: Robin Hood -- (Legendary character); Folklore -- England